X-ray computed tomography characterization of manufacturing induced defects in a glass/polyester pultruded profile. (1st July 2018) - Baran, Ismet; Straumit, Ilya; Shishkina, Oksana; Lomov, Stepan V.
Abstract: Critical assessment of the internal geometry after manufacturing of fiber reinforced polymer composites is essential for developing more reliable and robust production. In the present work, manufacturing induced defects such as fiber misalignment and porosity in a glass/polyester pultruded composite profile are evaluated. The internal geometry of the composite is characterized by X-ray micro-computed tomography (micro-CT) and analyzed using the VoxTex software which allows validated and detailed characterization of the internal geometry. Resin rich areas are observed in between the glass rovings at which the unidirectional fibers are misaligned with respect to the desired pulling direction. Results show that the misalignment in in-plane fiber orientation is more severe (30–40°) than the out-plane fiber orientation (10–20°). Two different types of porosities are quantified: the first one is discontinuous and located inside the resin rich areas; the second one is more severe and continuously located between the glass rovings. The area of the total continuous porosity is estimated approximately as 0.212–0.246 mm 2 per unit length in the pulling direction. The fiber misalignments and resin rich areas cause 15–20% reduction in the studied part stiffness in the longitudinal direction.